PUBLIC RELATIONS COMMUNICATION MODEL THROUGH CSR PROGRAMS DURING THE COVID-19 PANDEMIC - Thalia, Indi; Andrini, Susi (Transpublika Publisher, 2022)
The purpose of this study was to find out what the PR communication model carried out by The Body Shop was through its CSR program during the Covid-19 pandemic. Prior to the activity called “Bring Back Our Bottle” (BBOB), it has been implemented since 2008 and continues to this day. Problems that occurred when the Covid-19 pandemic hit the world so that communication that occurred to return used bottles of The Body Shop faltered, so it was necessary to do an effective way to keep it going. This recycling is to encourage customers to return various empty bottles to The Body Shop outlets to be reused and reused. This study uses a qualitative method with a descriptive approach. Data were obtained through in-depth interviews and also observations of informants. The results of this study indicate that The Body Shop's PR communication model through the CSR program during the pandemic under the theme